Administración de riesgos en las tecnologías de información - Campos Valdovinos, Yesenia (My University, 2012)
Administración de riesgos en las tecnologías de información
Administración de riesgos en las tecnologías de información
Keywords: Administración de riesgos en las tecnologías de información